Profiling of Sexually Dimorphic Genes in Neural Cells to Identify Eif2s3y, Whose Overexpression Causes Autism-Like Behaviors in Male Mice - Zhang, Muxian; Zhou, Yunqiang; Jiang, Yiru; Lu, Zhancheng; Xiao, Xiaoxia; Ning, Jinhuan; Sun, Hao; Zhang, Xian; Luo, Hong; Can, Dan; Lu, Jinsheng; Xu, Huaxi; et al. (Frontiers in Cell and Developmental Biology, 2021)
Many neurological disorders exhibit sex differences and sex-specific therapeutic responses. Unfortunately, significant amounts of studies investigating molecular and cellular mechanisms underlying these neurological disorders use primary cell cultures with undetermined sexes; and this may be a source for contradictory results among different studies and impair the validity of study conclusion. Herein, we comprehensively compared sexual dimorphism of gene expression in primary neurons, astrocytes, and microglia derived from neonatal mouse brains. We found that overall sexually dimorphic gene numbers were relatively low in these primary cells, with microglia possessing the most (264 genes), neurons possessing the medium (69 genes), and astrocytes possessing the least (30 genes). KEGG analysis indicated that sexually dimorphic genes in these three cell types were strongly enriched for the immune system and immune-related diseases. Furthermore, we identified that sexually dimorphic genes shared by these primary cells dominantly located on the Y chromosome, including Ddx3y, Eif2s3y, Kdm5d, and Uty. Finally, we demonstrated that overexpression of Eif2s3y increased synaptic transmission specifically in male neurons and caused autism-like behaviors specifically in male mice. Together, our results demonstrate that the sex of primary cells should be considered when these cells are used for studying the molecular mechanism underlying neurological disorders with sex-biased susceptibility, especially those related to immune dysfunction. Moreover, our findings indicate that dysregulation of sexually dimorphic genes on the Y chromosome may also result in autism and possibly other neurological disorders, providing new insights into the genetic driver of sex differences in neurological disorders.